The Deformation Characteristics of Weak Foundation with High Back Siltation in the Immersed Tunnel - Xiabing Yue; Yuan Xie; Yongli Xie (Advances in Materials Science and Engineering)
The deformation characteristics of a weak foundation with high back siltation in an immersed tunnel lack empirical data; however, the calculation method and control of foundation settlements are highly important to tunnel design and construction. This paper takes a cross section of the natural foundation of an immersed tunnel in the Hong Kong-Zhuhai-Macao Bridge (HZMB) as the research object and conducts a centrifuge model test. The soil layer is divided, and the soil parameters are determined by the CPTU and the indoor dynamic three triaxial test. In consideration of the actual engineering scale and the ability of the centrifuge model test system, the similarity ratio of the model to the prototype is studied and determined. As for the immersed tube structure, the deformation characteristics are mainly studied. Therefore, the organic glass is selected as the model material by the similarity of the elastic modulus and the density. The characteristics of the resilience and recompression of the natural foundation of the immersed tunnel and the strain characteristics of the immersed tube structure are obtained by the analysis of the multiworking condition test data. Moreover, based on the actual engineering geological conditions of the subsea tunnel, a numerical calculation method is carried out to check the reliability of the centrifuge model test results. The results of the numerical calculation are consistent with the model test results.